Advanced Solid-State Photonics (TOPS) 2005
DOI: 10.1364/assp.2005.139
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Wave Laser Operation of Yb^3+:YVO_4

Abstract: An Yb 3+ :YVO 4 laser under Ti:Al 2 O 3 laser pumping and diode laser pumping with a maximum output power of 433 mW at an emission wavelength of 1037 nm is presented. Furthermore Stark-splitting of both multiplets was determined for the first time by analysing absorption and fluorescence at low temperatures. The absorption and emission cross-sections as well as the fluorescence lifetime were determined. The absorption shows a maximum in π -polarization of 6.74×10 -20 cm 2 with a width of 8 nm. At the laser wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
4
8
0
Order By: Relevance
“…The output coupler had a radius of curvature (RC) equal to 25 mm. The fiber-coupled pump diode laser (diameter: 200 μm, NA=0.2) provided a maximum unpolarized output power of 50 W but at the somewhat lower pump powers used here the pump wavelength (975-981 nm) was not optimum for the studied vanadates where the peak Yb absorption for π-polarization occurs near 985 nm [1][2][3][4][5]. The pump beam was focused to a spot of about 200 µm (diameter) at the position of the crystals by a focusing optics with an imaging ratio of 1:1.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The output coupler had a radius of curvature (RC) equal to 25 mm. The fiber-coupled pump diode laser (diameter: 200 μm, NA=0.2) provided a maximum unpolarized output power of 50 W but at the somewhat lower pump powers used here the pump wavelength (975-981 nm) was not optimum for the studied vanadates where the peak Yb absorption for π-polarization occurs near 985 nm [1][2][3][4][5]. The pump beam was focused to a spot of about 200 µm (diameter) at the position of the crystals by a focusing optics with an imaging ratio of 1:1.…”
Section: Resultsmentioning
confidence: 91%
“…The maximum absorption/emission cross sections for the π-polarization near 985 nm are similar for the three vanadate hosts: 6.74×10 -20 cm 2 /8.30×10 -20 cm 2 in YVO 4 [1], 7.2×10 -20 cm 2 /9.0×10 -20 cm 2 in GdVO 4 (remeasured here), and 8.42×10 -20 cm 2 /11.8×10 -20 cm 2 in LuVO 4 [5]. The fluorescence decay times measured for the three hosts by the pinhole or powder methods range roughly from 250 to 350 µs [5].…”
Section: A977_1pdfmentioning
confidence: 80%
See 1 more Smart Citation
“…It was first developed as a laser host material for the trivalent neodymium ion (Nd 3+ ) in 2002. 1 Spectroscopic studies of Nd:LuVO 4 indicated larger absorption cross section near 800 nm and larger emission cross section at 1.064 µm in comparison with both Nd:YVO 4 and Nd:GdVO 4 . 1 These features are very desirable for diodepumped solid-state lasers, as they make it feasible to achieve highly efficient pumping and to realize low threshold laser operation with high optical-to-optical efficiency.…”
Section: Introductionmentioning
confidence: 91%
“…2 In 2006, LuVO 4 was doped also with thulium (Tm 3+ ) and with diode-pumping in the same 800 nm spectral range, cw laser operation near 1.9 µm was achieved. 3 Very recently, all the three vanadate crystals (YVO 4 , GdVO 4 , and LuVO 4 ) were demonstrated to be promising laser host materials for the ytterbium ion (Yb 3+ ). 4─7 The major advantages of Yb-doped vanadates, compared to Yb:YAG which has been widely employed since the early days of Yb-lasers, are the higher absorption and emission cross sections and the broader bandwidths, the small quantum defect which results from the much closer wavelengths of excitation and emission, and the inherent polarized oscillation arising from the strong anisotropy in the emission spectra.…”
Section: Introductionmentioning
confidence: 99%